Testing of Seeds of Some Tropical Tree Species for Germination and Mycoflora - Purohit, Mamta; , Jamaluddin; Mishra, G. P. (Indian Forester, 1996)
The seeas of Pithecelobium dulce, Tamrindus indica and Terminalia bellirica were collected from different localities of Madhya Pradesh. The germination of seeds was studied immediately after one month of collection and found more than 70 per cent germination on blotter paper as well as in soil mixture. Eight fungal species were isolated from the seeds of tested species. Aspergilli, Chaetomium sp., and Rhizopus stoloniler were associated with the seeds of all three species under study. The seed dressing with Bavistin, Dithane M-45, Thyride, F'ytolan and Ceresan @ 3 g per kg seed weight gave best control of majority of seed-born fungi.